Globalization in practice - Thrift, Nigel J.; Tickell, Adam; Woolgar, Steve; Rupp, William H. (Oxford, United Kingdom Oxford University Press, 2014)
The concept of globalization has become ubiquitous in social science and in the public consciousness and is often invoked as an explanation for a diverse range of changes to economies, societies, politics and cultures - both as a positive liberating force and as a wholly negative one.
aContents note continued: 36. How Rounders Goes around the World / Elizabeth Shove -- pt. V HEALTH AND NATURE -- 37. Biodiversity and Globalization / Geoffrey C. Bowker -- 38. Mobility and the Medical Image / Catelijne Coopmans -- 39.e-Solutions to Sharing Information in Child Protection: The Rise and Fall of ContactPoint / Sue White -- 40. Globalizing of Bananas: Of Rhizomes, Fungi, and Mobility / Mimi Sheller -- pt. VI ORDER AND CONTROL -- 41. Forms that Form / Nicholas Gill -- 42. Accounting for the Calculating Self / Peter Miller -- 43. Replaying Society to the World through CCTV / Daniel Neyland -- 44. The AK-47 as a Material Global Artefact / Tom Osborne -- 45. Human Rights / Sharyn Roach Anleu -- pt. VII CLASSIFICATIONS -- 46. Area-Based Classifications / Roger Burrows -- 47. First Names: Examples from Germany / Jurgen Gerhards -- 48. One of My Top Ten Days / Lucy Kimbell -- 49. Barcodes and RFIDs / Martin Dodge -- 50. ISO 9000 / Wendy Larner -- 51. Number / Helen Verran.
Includes bibliographical references and index.
Keywords: Globalization; Mondialisation